Dirty scapegoats: explaining Israel's ties with South Africa during the 1970s and 1980s - Alsheh, Yehonatan (Faculty of Humanities, University of the Free State, 2013)
The article surveys five possible explanations for the ties between Israel and South Africa between the 1970s and 1980s. (1) The Industrial-Military Complex Explanation, arguing that both the Israeli and South African defence establishments and arms industries had much to gain from such a relationship, and enough political influence to ensure that this would indeed happen. (2) The Nuclear Alliance Explanation, arguing that it was in Israel and South Africa’s national interest to forge a nuclear consortium that would enable them to attain and further develop significant nuclear capacities, conceived by both states as the ultimate means for guaranteeing the survival of their chronicallycontested regimes. (3) The Ideological Affinities / similar Regime-Type Explanation, arguing that, while Israel was unable or in any case reluctant to publicly admit it, it was not averse to the South African regime of separate development, mostly because, ever since 1967, it was on a course of constructing its own version of such a regime. (4) The Pariah States Alliance Explanation, arguing that Israel and South Africa shared the same international status of pariah states, hence having no other states they could befriend, and in any case nothing to lose from collaborating with each other. (5) The Politics of International Pariah-Making Explanation, arguing that the concept of the pariah state – which emerged in 1977 and disappeared by the end of the 1980s – was not a naïve scholarly attempt to conceptualize a new type of international actor, but rather an ideological construct, meant to re-justify the United State’s support for some of its more embarrassing client states, while restructuring the precise way in which that support was provided.
Keywords: Israel; Palestine; Palestine; Nuclear; Pariah; Foreign relations; Arms trade; Embargo; Apartheid; Occupation; United States of America; United Nations; International Law; South Africa